Efforts to improve nutritional knowledge in pregnant women through education on pregnant women's nutritional needs at bpm nurhenni s, s.st., kab.gowa - Muldaniyah, Muldaniyah; Asli, Kartika (Journal of Evidence-Based Community Health, 2025)
Abstract: During pregnancy, some of the nutrient requirements will increase. The important thing that must be considered by pregnant women is that the food consumed consists of a balanced menu composition. The purpose of this community service is to increase the knowledge of pregnant women about pregnancy nutrition. The facts found in the field are that there is low public knowledge about the importance of nutritionin pregnant women. The method of solving problems that is carried out is Education about providing ducation on the importance of nutrition to pregnant women. During the community service activities, 18 pregnant women attended the attendance. The results of the activity were obtained. Participants were enthusiastic about the extension material, none of the participants left the extension site during the extension process and more than 75% of the participants who attended were able to answer questions from the extension agents about the material presented. This proves that the participants pay attention to the material presented. The conclusion is that the provision of knowledge about the importance of nutrition in pregnant women has a positive impact on society, so that people understand the importance of nutrition in pregnant women. It is hoped that further counseling will focus on nutrition in the first, second and third trimesters of pregnant